The bug book - Fliess, Sue (New York, New York : Grosset & Dunlap, an imprint of Penguin Random House, 2016)
This fun rhyming story lists all the bugs you can imagine$1 (Bcreep bugs, climb bugs, sticky-slime bugs! Discover the vast world of insects in this photo-filled book.s
Ages 3 to 5.
Keywords: Insects -- Juvenile literature; Picture books for children